KOMUNIKASI INTERPERSONAL CUSTOMER SERVICE TRAVEL UMRAH DALAM PELAYANAN JAMAAH (STUDI DESKRIPTIF PADA BB TOUR & TRAVEL KARAWANG) - Annisaa Rizjun; Rastri Kusumaningrum; Tikka Muslimah (Sekolah Tinggi Agama Buddha Negeri Raden Wijaya, 2026)
This study was motivated by the importance of pilgrims’ trust in Umrah travel services, which is influenced by the quality of customer service interpersonal communication. The study aims to analyze how customer service interpersonal communication in Umrah pilgrim services builds pilgrims’ trust. The study employs a qualitative approach using a descriptive method. Data were collected through interviews with customer service representatives and the business owner, supplemented by documentation in the form of pilgrim questionnaires. Data analysis was conducted through data reduction, data presentation, and drawing conclusions. The results indicate that customer service interpersonal communication fosters pilgrim trust through three primary patterns: informative communication during the registration phase, educational communication during the manasik phase, and ongoing communication during the pre-departure preparation phase. Furthermore, consistent verbal and nonverbal communication helps strengthen the relationship between customer service representatives and pilgrims. Thus, customer service interpersonal communication plays a crucial role in building pilgrims’ trust through the clear delivery of information, empathetic attitudes, and continuous interaction throughout the service process.